2022
DOI: 10.1111/ppc.13125
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cognitive‐behavioral therapy on death anxiety and depression in patients with heart failure: A quasi‐experimental study

Abstract: Purpose: In this study, the effect of cognitive-behavioral therapy (CBT) on death anxiety and depression was investigated in patients with heart failure. Design and Methods:In this quasi-experimental study, 66 patients with heart failure were randomly assigned to intervention (n = 33) and control (n = 33) groups. Data collection was done using a demographic questionnaire, Templer death anxiety scale, and Beck depression inventory. Findings: It was found that the overall scores of death anxiety and depression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Our analysis encompassed 15 RCTs in total, involving a cohort of 926 patients. The interventions in experimental group comprised the following: spiritual care (1 study) ( Amini et al, 2020 ), group logotherapy (2 studies) ( Emafti et al, 2019 ; Heidary et al, 2023 ), acceptance and commitment therapy (3 studies) ( Farahi and Khalatbari, 2019 ; Sahebanmaleki et al, 2021 ; Fadhil et al, 2022 ), cognitive-behavioral therapy (2 studies) ( Moradi et al, 2022 ; Saki et al, 2022 ), logotherapy (2 studies) ( Akbari et al, 2021 ; Bahar et al, 2021 ), rational-emotive hospice care therapy (1 study) ( Onyechi et al, 2016 ), spirituality therapy training (1 study) ( Ameri et al, 2021 ), positive psychology group therapy (1 study) ( Saeedi et al, 2016 ), mindfulness based cognitive therapy (1 study) ( Nabipour et al, 2018 ), and white noise and Benson’s relaxation technique (1 study) ( Ahmadi et al, 2022 ). Thirteen studies utilized TDAS as an outcome indicator.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis encompassed 15 RCTs in total, involving a cohort of 926 patients. The interventions in experimental group comprised the following: spiritual care (1 study) ( Amini et al, 2020 ), group logotherapy (2 studies) ( Emafti et al, 2019 ; Heidary et al, 2023 ), acceptance and commitment therapy (3 studies) ( Farahi and Khalatbari, 2019 ; Sahebanmaleki et al, 2021 ; Fadhil et al, 2022 ), cognitive-behavioral therapy (2 studies) ( Moradi et al, 2022 ; Saki et al, 2022 ), logotherapy (2 studies) ( Akbari et al, 2021 ; Bahar et al, 2021 ), rational-emotive hospice care therapy (1 study) ( Onyechi et al, 2016 ), spirituality therapy training (1 study) ( Ameri et al, 2021 ), positive psychology group therapy (1 study) ( Saeedi et al, 2016 ), mindfulness based cognitive therapy (1 study) ( Nabipour et al, 2018 ), and white noise and Benson’s relaxation technique (1 study) ( Ahmadi et al, 2022 ). Thirteen studies utilized TDAS as an outcome indicator.…”
Section: Resultsmentioning
confidence: 99%
“…This research seeks to explore and compare these interventions, providing evidence-based insights into their effectiveness in reducing death anxiety among patients. Several therapeutic approaches, such as spiritual care, group logotherapy, acceptance and commitment therapy, cognitive-behavioral therapy, and rational-emotive hospice care therapy have been empirically proven to effectively alleviate the experience of DA in patients ( Onyechi et al, 2016 ; Saeedi et al, 2016 ; Nabipour et al, 2018 ; Emafti et al, 2019 ; Farahi and Khalatbari, 2019 ; Amini et al, 2020 ; Akbari et al, 2021 ; Ameri et al, 2021 ; Bahar et al, 2021 ; Sahebanmaleki et al, 2021 ; Ahmadi et al, 2022 ; Fadhil et al, 2022 ; Moradi et al, 2022 ; Saki et al, 2022 ; Heidary et al, 2023 ). This meta-analysis exclusively includes randomized controlled trials (RCTs) to ensure the highest level of evidence and minimize bias.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the site of included trials, four trials were conducted in the USA [ 20 23 ]. Two studies were conducted in Iran [ 24 , 25 ], and one study was conducted in the Philippines [ 19 ] The least follow-up period was one month [ 25 ], and the most extended follow-up period was 32 weeks [ 22 ]. Further details regarding CBT details and studies’ conclusion are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Neither the 2021 ESC HF guidelines (Wilkowska et al, 2022) nor the 2022 AHA/ACC/HFSA guidelines (Heidenreich et al, 2022) give a specific recommendation to address depression in patients with HF, because conventional therapies such as antidepressants have not been effective at improving outcomes. Studies show that Cognitive Behavioral Therapy (CBT) (Moradi et al, 2022a), physical exercise (Blumenthal et al, 2012), blended collaborative care (Rollman et al, 2021), and early palliative care (Romanò et al, 2020) reduce depression in patients with HF.…”
Section: Discussionmentioning
confidence: 99%